Control of interferon-τ gene expression by Ets-2 - Ezashi, Toshihiko (The National Academy of Sciences, 1998)
Expression of the multiple interferon-τ (IFN-τ) genes is restricted to embryonic trophectoderm of ruminant ungulate species for a few days in early pregnancy. The promoter regions of these genes are highly conserved. A proximal (bp −91 to −69) sequence has been implicated in controlling trophoblast-specific expression. Here it was used as a target for yeast one-hybrid screening of a day 13 conceptus cDNA library. Two transcription factors of the Ets family, Ets-2 and GABPα, were identified, consistent with the observation that active ovine IFN-τ genes contain a single 10-bp Ets motif (core: GGAA) in the proximal segment, whereas three known inactive ovine genes contain a mutated core motif (TGAA). Cotransfection of a promoter- (−126 to +50) luciferase reporter construct from an active gene (bovineIFN-τ1; boIFNT1) and an Ets-2 expression plasmid in human JAr cells provided up to a 30-fold increase in reporter expression, whereas promoters from inactive genes were not transactivated. GABPα alone was ineffective and had only a ≈2-fold positive effect when coexpressed with its partner GABPβ. Other Ets-related transcription factors, which were not detected in the genetic screen, also provided a range of lesser transactivation effects. Coexpression of Ets-2 and activated Ras failed to transactivate the IFNT promoter greater than Ets-2 alone in JAr cells. The presence of Ets-2 in nuclei of embryonic trophectoderm was confirmed immunocytochemically. Together, these data suggest that Ets-2 plays a role in the transient expression of the nonvirally inducible IFNT genes.